Family Experience while Caring for Covid-19 Patients during Home Quarantine - Armi Mawaddah; Dewi Elizadiani Suza; Amira Permatasari Tarigan (Jurnal Keperawatan, 2022)
Coronavirus Disease 2019 (COVID-19) is concerning health issue that the world, particularly Indonesia, deals with. The number of COVID-19 cases in Indonesia is growing. The role of the family in providing care to the COVID-19 patient with mild and moderate symptoms during home quarantine should be given a serious concern to prevent virus transmission to other family members. This study aims to into the family’s experience in Medan while caring for a family member infected with COVID-19 during a home quarantine. The purposive sampling technique is employed to select the 10 participants for this qualitative with phenomenological design research. And indepth interview is conducted as a data collection method, and then the data are analyzed using the Collaizzi method. The findings address six issues that the family experiences while providing health care to the COVID-19 infected family member during home quarantine : family burdens, family healthcare, support, the impact on families of COVID-19 patients, family barriers and family expectation. The family caring for the COVID-19 patient experiences several challenges and seeks support from other family members to obtain information for the patients recovery.